The Influence of Raw Material Inventory Control on the Production Process at PT. Dayup Indo in North Jakarta - Apriani, Nur; Sari, Sukarni Novita (Logistica : Journal of Logistic and Transportation, 2023)
This study aims to determine how much influence the control of raw material inventories on the production process at PT. Dayup Indo. The population in this study is the entire number of employees in the production and warehouse. This study uses a quantitative method. The sample in this study were 60 people with Non Probability Sampling technique, namely saturated Sampling. The independent variable in this study is the control of raw material inventory, while the dependent variable is the production process. Simple linear regression test results obtained Y = 4.215 + 0.728X which means that the value of 4.215 with 0.728 which states the effect of variable X on Y is positive. Based on regression analysis (t-test), it is known that t-value > t-table is 9.757 > 1.672 which means that raw material inventory control affects the production process at PT. Dayup Indo. With the coefficient of determination (R2) has a value of 0.621 indicates that the magnitude of the influence of raw material inventory control variables on variables of the production process is 62.1% while the remaining 37.9% is influenced by other objects that are not included in this study.